Positioning Techniques for Stroke Infarction Patients to Prevent Decubitus Wounds - Sujatmiko; Wahyu Sri Astuti (KHD Production, 2023)
Stroke is one of the leading causes of death and neurological impairment in Indonesia. This brain attack is a medical emergency that must be treated quickly, precisely, and carefully. This research aims to determine the effect of positioning techniques on the incidence of decubitus in stroke infarction patients. The research design used was a pre-experiment with a static group comparison design approach. The sampling technique used in this research was purposive sampling, with a total sample of 24 respondents. The treatment group consisted of 12 respondents, and the control group consisted of 12 respondents. After being evaluated for a month, the Chi-Square test results were obtained with a p-value of 0.013, which means less than 0.05; this means there is an influence between positioning and the incidence of pressure ulcers. In the treatment group, the results showed that ten respondents did not experience pressure ulcers after treatment; in the control group, eight suffered from pressure ulcers. This can occur due to patient compliance and the surrounding environment in activities such as tilting left and right to prevent pressure ulcers. This positioning action, carried out between 2-3 hours can make blood circulation in the body run smoothly, so this can reduce the incidence of pressure ulcers in patients who are lying down in bed.